CONCEPTUAL DIRECTIONS OF DEVELOPMENT OF THE INDUSTRY OF THE EURASIAN ECONOMIC UNION - A. Gibadullin (Вестник СибАДИ)
The article considers the preconditions for the emergence, formation and development of the Eurasian Economic Union, within which common markets for goods and services are created, a free flow of capital and labor is ensured, and strategic tasks are set for convergence of national industries into a common supranational industrial complex. The analysis of the industrial potential of the member states of the Eurasian Economic Union showed that there is a tendency to a fall in the volume of manufactured industrial products and a reduction in investments in fixed assets. Based on the results obtained, the article outlines the mechanisms for developing the industrial potential of the Eurasian Economic Union.